Ferulic acid attenuates liver fibrosis and hepatic stellate cell activation via inhibition of TGF-β/Smad signaling pathway - Mu M; Zuo S; Wu RM; Deng KS; Lu S; Zhu JJ; Zou GL; Yang J; Cheng ML; Zhao XK (Dove Medical Press, 2018)
Mao Mu,1,* Shi Zuo,2,* Rong-Min Wu,3 Kai-Sheng Deng,1 Shuang Lu,1 Juan-Juan Zhu,1 Gao-Liang Zou,1 Jing Yang,1 Ming-Liang Cheng,1 Xue-Ke Zhao1 1Department of Infectious Diseases, The Affiliated Hospital of Guizhou Medical University, Guiyang, Guizhou, China; 2Department of Hepatobiliary Surgery, The Affiliated Hospital of Guizhou Medical University, Guiyang, Guizhou, China; 3Department of Ultrasonography, The Maternity Hospital of Guizhou, Guiyang, Guizhou, China *These authors contributed equally to this work Purpose: Liver fibrosis is a worldwide health issue. Development of effective new drugs for treatment of this disease is of great importance. This study investigated the therapeutic effects of ferulic acid on liver fibrosis in vitro and in vivo.Materials and methods: Human hepatic stellate cell line (HSC) LX-2 was used for in vitro assays. Transforming growth factor β1 (TGF-β1) was used to induce hepatic fibrosis in LX-2 cells. Western blot was used to detect protein levels of collagen I, fibronectin, α-smooth muscle actin (SMA), p-Smad2, p-Smad3, p-p38, and p-JNK. Gene expression was measured by RT-qPCR. Fluorescence staining was used to determine localization of Smad4. CCl4-induced hepatic fibrosis in SD rats was used as an in vivo model. Histological features were detected by hematoxylin and eosin staining. Levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), hexadecenoic acid (HA), and hydroxyproline (Hyp) were measured by ELISA.Results: TGF-β1 treatment significantly increased levels of collagen I, fibronectin, α-SMA, p-Smad2, p-Smad3, and Smad4 in LX-2 cells. Ferulic acid improved TGF-β1-induced hepatic fibrosis via regulation of the TGF-β1/Smad pathway. Consistent with in vitro data, CCl4 caused severe hepatic fibrosis in SD rats, as determined by ALT, AST, HA, and Hyp upregulation. Protein levels of p-Smad2 and p-Smad3 in liver tissues were significantly increased following treatment with CCl4. All CCL4-induced changes were markedly attenuated by ferulic acid treatment.Conclusion: Ferulic acid potently improved hepatic fibrosis via inhibition of the TGF-β1/Smad pathway in vitro and in vivo. These findings provided evidence for potential use of ferulic acid to treat or prevent liver fibrosis. Keywords: ferulic acid, TGF-β1, CCl4, hepatic fibrosis, Smad signaling pathway